Rethinking place marketing: A literature review - Krister Olsson; Elin Berglund (European Regional Science Association (ERSA), 2010)
In contemporary western cities, city marketing is widely applied as a means for local economic development, city competitiveness and attractiveness. In practice, city marketing generally includes a wide range of promotional, organisational and spatial strategies and activities. It is often manifested in city centre revitalization including upgrading of public space, the construction of spectacular entertainment and cultural amenities, and image enhancing activities. Parallel to the growing practice of city marketing, there has been a growing interest in city marketing within the academia. However, the literature on city marketing is by no means homogenous. City marketing is interpreted, described and valued in very different ways and there is, apparently, diverging opinions what city marketing is and what it means to a city and its citizens. Furthermore, the literature on city marketing tends to make general assumptions about the prevalence and nature of city marketing practice and fails to consider local and regional variations. Most empirical studies are concerned with big cities in international competition. To a great extent, there is a lack of knowledge in how city marketing is performed in small and medium-sized cities in a regional context. The aim with the paper is to contribute with empirical and theoretical knowledge about the prevalence, nature and meaning of city marketing by focusing Swedish small and medium-sized cities in various regional contexts. Through a review of city marketing literature, the development of a theoretical framework of city marketing, and an empirical study of city marketing practice in all Swedish municipalities, the paper is expected to contribute with new knowledge about both the practice and theory of city marketing.
Keywords: 330